Degarelix vs. leuprorelin for the treatment of prostate cancer in China: A cost-utility analysis - Yan, Jianzhou; Li, Caiyun; Zhang, Xuefang; Cheng, Luyan; Ding, Ruilin; Zhang, Lingli (Frontiers in Public Health, 2022)
Objective: To explore the cost-effectiveness of degarelix acetate for injection (degarelix) compared to leuprorelin in prostate cancer (Pca) castration treatment from Chinese healthcare system perspective. Methods: A Markov model, adapted from the one established in Finland was conducted for the cost-effectiveness analysis of degarelix and leuprorelin for Pca treatment. The main data were derived from global phase III clinical trials of degarelix (CS21), published study and expert surveys. Outcomes, utility and costs of prostate cancer patients were calculated on a 30-year time horizon. The CS21 study based population of intention-to-treat (ITT) population and 3 scenarios were modeled. Taking three times of the Gross domestic product (GDP) per capita (242,928 yuan, 2021) as the acceptable threshold for cost-effectiveness. One-way and probabilistic sensitivity analyses were performed on key parameters, including transition probabilities, costs, utility, and discount rate to test the robustness of the model. Results: Base case analysis for ITT population revealed that total costs of degarelix and leuprorelin were 566,226 yuan and 489,693 yuan, while the total quality-adjusted life years (QALYs) were 5.19 and 4.51 during the 30-year time horizon, resulting an incremental cost effectiveness ratio (ICER) of 112,674 yuan/QALY which was 1.39 times the GDP per capita, lower than willingness-to-pay level of three times the GDP per capita. The results for scenario analyses revealed that compared to leuprorelin, degarelix for Pca treatment in China was cost-effective. One-way sensitivity analysis showed that the model was most sensitive to price of 80 mg degarelix, utility of 1st-line therapy, hazard ratio of PSA recurrence, price of 3.75 mg leuprorelin, response rate of docetaxel per cycle, and discount rate of cost. In probabilistic sensitivity analysis, compared to leuprorelin, the probability of degarelix to be cost-effective was 53% and 81% for willingness-to-pay threshold of 1 and 3 times the GDP per capita. Conclusion: Compared to leuprorelin, degarelix for prostate cancer treatment is cost-effective. Moreover, scenario, one-way, and probabilistic sensitivity analyses revealed that the model was robust.